Sustainability and cost - benefit analysis - Pires, Cesaltina (2010)
In this paper I address the issue of incorporating environmental sustainability in project appraisal. I extend the results of Barbier,Markandya, and Pearce on 'operationalizing' a concept of sustainability into appraisal methods for practical decisionmaking. I generalize their results in two directions. First, I abandon their implicit assumption that benefits and costs of a given project in a given period depend only on the level of activity of the project in the same period. Second, I address the issue of which portfolio of projects to choose. My results show how to modify the net present value criterion for choosing a set of projects in the presence of a sustainability constraint.